Reforestation, Landscape Conservation, and the Anxieties of Empire in French Colonial Algeria. - Ford, Caroline (American Historical Review, 2008)
This article examines the historical impact of Europeans and colonialism on the environment, specifically that of Algeria. The French, who colonized Algeria, began certain environmental policies with regards to local forests. After invasion in 1830, the French imposed their laws and restriction on Algerian forests, which did not exclude commercial logging. Much of European concern over the environment in their colonies sprang from an anxiety that their colonists would not be able to, or want, to live there comfortably.